2007
DOI: 10.2119/2006-00057.fujita
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin Expression in the Liver: Relatively Low Level in Patients with Chronic Hepatitis C

Abstract: Patients with chronic hepatitis C frequently have serum and hepatic iron overload, but the mechanism is unknown. Recently identified hepcidin, exclusively synthesized in the liver, is thought to be a key regulator for iron homeostasis and is induced by infection and inflammation. This study was conducted to determine the hepatic hepcidin expression levels in patients with various liver diseases. We investigated hepcidin mRNA levels of liver samples by real-time detection-polymerase chain reaction; 56 were hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
136
3
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(156 citation statements)
references
References 48 publications
16
136
3
1
Order By: Relevance
“…A similar observation has been reported in patients with various liver diseases. Fujita et al [14] demonstrated that the serum ferritin level had a strong positive correlation with the hepatic level of hepcidin mRNA expression. In cultured cell models, a direct relation between ferritin and hepcidin expression in hepatocytes has not been demonstrated so far.…”
Section: Discussionmentioning
confidence: 99%
“…A similar observation has been reported in patients with various liver diseases. Fujita et al [14] demonstrated that the serum ferritin level had a strong positive correlation with the hepatic level of hepcidin mRNA expression. In cultured cell models, a direct relation between ferritin and hepcidin expression in hepatocytes has not been demonstrated so far.…”
Section: Discussionmentioning
confidence: 99%
“…22 Hepcidin was lower in CHC patients than in CHB patients. 23 Hepcidin and TfR2 may play a role in the pathogenesis of iron overload in CHC patients. Decreased hepcidin levels and increased TfR2 levels contribute to delivery of iron to hepatocytes from macrophage iron stores and intestinal mucosa.…”
mentioning
confidence: 99%
“…The peptide HRSKAbuGMC was used as antigen for the production of monoclonal antibodies. Among the generated antibodies, mHK(8) and mHK (9) showed the best antigen recognition and were chosen for further evaluation and characterization. In dot blot and Western blot assays, both antibodies specifically detected the antigen HRSKAbuGMC as well as synthetic hepcidin.…”
Section: Discussionmentioning
confidence: 99%
“…3 Immunofluorescence staining with the monoclonal antibodies mHK(8) and mHK (9). Immunofluorescence staining of human liver tissues using the monoclonal antibodies mHK(8), mHK (9) (Fig.…”
Section: Evaluation Of Hepcidin Measurement In Patients With Iron Dismentioning
confidence: 99%
See 1 more Smart Citation